2018
DOI: 10.1159/000493653
|View full text |Cite
|
Sign up to set email alerts
|

Apelin-13 Administration Protects Against LPS-Induced Acute Lung Injury by Inhibiting NF-κB Pathway and NLRP3 Inflammasome Activation

Abstract: Background/Aims: Acute lung injury (ALI) is induced by a variety of external and internal factors and leads to acute progressive respiratory failure. Previous studies have shown that apelin-13 can decrease the acute lung injury induced by LPS, but the specific mechanism is unclear. Therefore, a mouse lung injury model and a cell model were designed to explore the mechanism of how apelin-13 alleviates the acute lung injury caused by LPS. Methods: The effect of apelin-13 on LPS-induced structural damage was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 47 publications
3
45
0
Order By: Relevance
“…These cytokines are released to induce selective recruitment of monocytes, neutrophils and lymphocytes, eventually causing pyroptosis, a novel form of programed cell death (34,35), which leads to tissue damage as a consequence. ali/ardS pathogenesis is closely associated with the NLRP3 inflammasome in lipopolysaccharide (lPS)-induced mouse and macrophage models (36), in lPS-induced animal models of ali (36,37), and in cecal ligation perforation (38). The present study demonstrated that nlrP3, aSc and caspase-1 expression levels were elevated in the ali group, which was consistent with the aforementioned studies.…”
Section: Discussionsupporting
confidence: 91%
“…These cytokines are released to induce selective recruitment of monocytes, neutrophils and lymphocytes, eventually causing pyroptosis, a novel form of programed cell death (34,35), which leads to tissue damage as a consequence. ali/ardS pathogenesis is closely associated with the NLRP3 inflammasome in lipopolysaccharide (lPS)-induced mouse and macrophage models (36), in lPS-induced animal models of ali (36,37), and in cecal ligation perforation (38). The present study demonstrated that nlrP3, aSc and caspase-1 expression levels were elevated in the ali group, which was consistent with the aforementioned studies.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, GSK developed a recombinant human ACE2, GSK2586881 for treatment of acute respiratory distress syndrome (ARDS) and showed that this molecule was well-tolerated in clinical trials 49 . Corroborating on this, apelin signalling induces ACE2 expression in failing hearts 12 , and protects against lung injury in experimental models of acute respiratory distress syndrome 50 , possibly by inhibiting the NF-κB pathway and components of the inflammasome 51 . Furthermore, apelin counteracts the effects of angiotensin-II signalling, which is negatively regulated by ACE2, suggesting that targeting ACE2 and apelin could be a potentially novel therapeutic strategy for treatment of lung injury related pathologies and heart failure.…”
Section: Discussionmentioning
confidence: 91%
“…Apelin protects against apoptosis in cardiac tissues by regulating FoxO1 in mice [40] and by upregulating Bcl-2 and downregulating Bax together with cleaved caspase-3 in rats [41]. In addition, apelin alleviates oxidative stress and mitochondria-mediated apoptosis in mice [42]. Apelin induces expression of the antiapoptotic protein B cell lymphoma 2 and decreases production of the proapoptotic protein Bax in osteoblasts [43].…”
Section: Discussionmentioning
confidence: 99%